Identification of four compounds from the Pharmakon library with antifungal activity against Candida auris and species of Cryptococcus. (16th May 2022) - de Oliveira, Haroldo C; Castelli, Rafael F; Alves, Lysangela R; Nosanchuk, Joshua D; Salama, Ehab A; Seleem, Mohamed; Rodrigues, Marcio L
Abstract: There is an urgent need to develop novel antifungals. In this study, we screened 1600 compounds for antifungal activity against Cryptococcus neoformans and Candida auris . We evaluated 4 promising compounds against 24 additional isolates of Cr. neoformans, Ca. auris, Cr. deuterogattii, and Cr. gattii . The four compounds, dequalinium chloride (DQC), bleomycin sulfate (BMS), pentamidine isethionate salt (PIS), and clioquinol (CLQ), varied in their efficacy against these pathogens but were generally more effective against cryptococci. The compounds exerted their antifungal effect via multiple mechanisms, including interference with the capsule of cryptococci and induction of hyphal-like morphology in Ca. auris . Our results indicate that DQC, BMS, PIS, and CLQ represent potential prototypes for the future development of antifungals. Lay Summary: Fungal infections can be lethal and the options to fight them are scarce. We tested 1600 molecules for their ability to control the growth of two important fungal pathogens, namely Candida auris and species of Cryptococcus . Four of these compounds showed promising antifungal activities.